Effect of pectin on the interactions among phenolic compounds determined by antioxidant capacity - Alvarez-Parrilla, Emilio (2020)
Antioxidant capacity of the phenolic compounds depends on their chemical structures and interactions between them. Twenty binary combinations between four phenolic acids (gallic acid, coumaric acid, chlorogenic acid, caffeic acid) and four flavonoids (catechin, quercetin, epicatechin, and rutin) were analyzed to evaluate the effect of their combinations by DPPH and FRAP methods. Isobolograph analysis and combination index (CI) were used for DPPH, and the percentage of differentiation for FRAP method to evaluate the effect of the PC binary combinations (synergism, additive or antagonism). Chlorogenic acid presented the highest inhibition of DPPH, while coumaric acid did not present any DPPH inhibition. Gallic acid and catechin showed better ferric reducing capacit. The antioxidant capacity increased when pectin is mixed with individual PC. The isobologram method shows that the PC binary combinations …